Factors Affecting Growth and β-carotene Content of Chlorosarcinopsis sp. (PSU/CHL20) in Batch Culture - Wongsnansilp, Tassnapa; Tansakul, Pimpan; Arunyanart, Manop (Agriculture and Natural Resources, 2007)
The effect of light intensity, potassium nitrate concentrations and temperature on the growth and β-carotene content of Chlorosarcinopsis sp. (PSU/CHL20) were determined. In the first experiment, algal cells were grown on a shaker in Erlenmeyer flasks containing 150 ml of NSIII medium and at a shaking speed of 150 rpm. Potassium nitrate concentrations were 0, 0.1 and 0.2 g l-1. Light intensities used were 60, 120 and 180 μmolm-2s-1. The light / dark cycle was 16:8 h and the temperature was controlled at 25°C. The optimum light intensity and potassium nitrate concentration for algal growth and β-carotene content was 120 μmolm-2s-1 and 0.1 g l-1 which produced a maximum cell number of 138×105 cell ml-1and a β-carotene content of 0.133 mg l-1, (0.012 pg cell-1) respectively. In the second experiment, the effect of temperature on the growth and β-carotene content was investigated. In this experiment the light intensity was 120 mmolm-2s-1 and the potassium nitrate concentration was 0.1g l-1, at temperatures of 25°C, 30°C and 35°C. Although statistically insignificant (P>0.05), the algal growth increased slightly with increasing temperature. The highest cell numbers of 148x105 cell ml-1 were obtained at 30°C on day 14 of cultivation. The maximum β-carotene content of 0.543 mg l-1 (0.052 pg cell-1) was achieved at 30°C and this was significantly higher than that of the culture grown at 25°C (P<0.05).